2012
DOI: 10.1002/joc.3603
|View full text |Cite
|
Sign up to set email alerts
|

An asynchronous regional regression model for statistical downscaling of daily climate variables

Abstract: ABSTRACT:The asynchronous regional regression model (ARRM) is a flexible and computationally efficient statistical model that can downscale station-based or gridded daily values of any variable that can be transformed into an approximately symmetric distribution and for which a large-scale predictor exists. This technique was developed to bridge the gap between large-scale outputs from atmosphere-ocean general circulation models (AOGCMs) and the fine-scale output required for local and regional climate impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
139
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(139 citation statements)
references
References 59 publications
0
139
0
Order By: Relevance
“…For example, Abatzoglou and Brown (2012), Stoner et al (2013), Ahmed et al (2013) each applied quantile mapping to daily climate model data that had been interpolated to a high-resolution observational grid. However, Maraun (2013) and Gutmann et al (2014) demonstrated that this approach-applying a univariate bias correction algorithm to interpolated climate data at individual grid points-can lead to fields with unrealistic spatial structure, especially if the variable being downscaled operates on spatial scales that are substantially finer than the climate model grid.…”
Section: Spatial Precipitation Examplementioning
confidence: 99%
“…For example, Abatzoglou and Brown (2012), Stoner et al (2013), Ahmed et al (2013) each applied quantile mapping to daily climate model data that had been interpolated to a high-resolution observational grid. However, Maraun (2013) and Gutmann et al (2014) demonstrated that this approach-applying a univariate bias correction algorithm to interpolated climate data at individual grid points-can lead to fields with unrealistic spatial structure, especially if the variable being downscaled operates on spatial scales that are substantially finer than the climate model grid.…”
Section: Spatial Precipitation Examplementioning
confidence: 99%
“…The ESD method examined is a variant of the asynchronous regional regression model (ARRM version 1) of Stoner et al (2013) and the variable of interest is daily maximum near-surface air temperature (tasmax). The ARRM is one of a widely-used class of ESD methods that operate on the distributional characteristics of data samples.…”
Section: Perfect Model Experiments Using the Arrm Downscaling Methodsmentioning
confidence: 99%
“…For extreme values, output from the ARRM statistical downscaling method, which includes bias-correction and cross-validation, showed improved accuracy and ability to be efficient and generalizable across regions (Stoner et al 2013). For precipitation (and other variables), the MACA method has been found to outperform the BiasCorrected Spatial Disaggregation method (BCSD), used to create the Bureau of Reclamation dataset, due to the ability to jointly downscale certain variables (Abatzoglou and Brown 2012).…”
Section: Climate Model Reliabilitymentioning
confidence: 99%